Associations between barriers to self-care and diabetes complications among patients with type 2 diabetes. (July 2018) - Sina, Maryam; Graffy, Jonathan; Simmons, David
Highlights: A comprehensive framework can be used to describe barriers to care. People with diabetes in England face a multitude of barriers to care. Barriers to care are more common when diabetes related complications exist. Psychological barriers were the most frequent barriers. Psychological barriers were more common in those with diabetes complications. Abstract: Aims: To determine which barriers to care are associated with type 2 diabetes complications in an area in rural East England. Methods: 3649 individuals with type 2 diabetes from 62 general practices were contacted via postal invitation which included a 33 item Barriers-to-Diabetes-Care Survey. Barriers were grouped into five priori major categories: educational, physical, psychological, psychosocial, and systems. The associations of reported barriers, both individually and as a group, with self-reported complications were assessed using logistic regression. Results: 39.5% of participants had self-reported diabetes complications. Physical health barriers (OR = 3.3; 95%CI: 2.7, 4.0), systems barriers (OR = 1.6; 95%CI: 1.3, 2.0) and psychological barriers (OR = 1.3 (95%CI: 1.1, 1.5) were associated with diabetes complications. In subcategories, presence of comorbidities (OR = 4.8; 95%CI: 3.9, 5.9), financial difficulties (OR = 1.7; 95%CI: 1.3, 2.1), absence of services (OR = 2.0; 95%CI: 1.4, 3.0), feeling others should bear more financial responsibility for their care (OR = 1.6 (95%CI: 1.1, 2.1), no access to diabetes service (OR = 1.3; 95%CI: 1.1, 1.5), feeling worried about their diabetes (OR = 1.5; 95%CI: 1.2, 2.0) and lack of readiness to exercise (OR = 1.4; 95%CI: 1.2, 1.7) were associated with diabetes complications. Conclusions: Barriers to self-care are significantly more common among those with, than those without, diabetes complications. Systematic identification and management of different barriers to self-care could help personalise care for those with diabetes related complications.